Acute posterior multifocal placoid pigment epitheliopathy associated with diffuse retinal vasculitis and late haemorrhagic macular detachment. - Isashiki, M (1986)
A 20-year-old healthy man suffered rapid loss of bilateral central vision with placoid lesions at the level of the retinal pigment epithelium and choriocapillaris scattered in the posterior pole of the fundus. In addition, acute vasculitis of the retinal veins was remarkable and widespread throughout the posterior pole and midperiphery. These inflammatory signs subsided in several weeks and were succeeded by recovery of the normal visual acuity with residual pigment derangements in the deep retina. Sixteen months after the onset of the disease choroidal neovascular membranes developed in the macular region of the left eye, followed by haemorrhagic macular detachment and marked visual loss. Significant increases in the serum cold agglutinin titre occurred as isolated laboratory findings concurrently with the acute stage of the disease and the late macular complication, though no clinical or other laboratory sign suggested viral infection.